Institute for Scientific Information sales team meeting - Benson, Neil (1980)
A black and white photograph depicting the Institute for Scientific Information (ISI) sales team. The group of ten people captured in-frame are pictured sitting around a table. One man stands to address the group. A sign hanging in the background reads "100% + Achievement / Congratulations to ISI Field Sales." The ISI was an academic publishing service, founded by Eugene Garfield (1925-2017) in Philadelphia in 1956. ISI offered scientometric and bibliographic database services and specialized in citation indexing and analysis
Keywords: Garfield, Eugene; Information science; Information storage and retrieval systems; Citation indexes; Science publishing; Science--Information services; Institute for Scientific Information